Plasma AR status and cabazitaxel in heavily treated metastatic castration-resistant prostate cancer. (July 2019) - Conteduca, Vincenza; Castro, Elena; Wetterskog, Daniel; Scarpi, Emanuela; Jayaram, Anuradha; Romero-Laorden, Nuria; Olmos, David; Gurioli, Giorgia; Lolli, Cristian; Sáez, Maria Isabel; Puente, Javier; Schepisi, Giuseppe; et al.
Abstract: Background: Plasma androgen receptor (AR) copy number status has been identified as a potential biomarker of response in patients with metastatic castration-resistant prostate cancer (mCRPC) receiving docetaxel or the AR-targeted therapies abiraterone or enzalutamide. However, the relevance of plasma AR status in the context of cabazitaxel therapy is unknown. Patients and methods: Between September 2011 and January 2018, pretherapy plasma samples were collected from 155 patients treated with second- or third-line cabazitaxel at standard or reduced dose in different biomarker protocols. Droplet digital polymerase chain reaction was used to identify plasma AR gain and normal samples. The primary objective was to evaluate associations of plasma AR status with treatment outcome. In an exploratory analysis, a comparison between plasma AR and treatment type was investigated by incorporating updated data from our prior study of 85 post-docetaxel patients receiving abiraterone or enzalutamide. Results: We observed a shorter median overall survival (OS) and progression-free survival (PFS) in AR -gained compared to AR -normal patients (OS 10.5 versus 14.1 months, hazard ratio (HR) = 1.44, 95% confidence interval [CI] 0.98–2.13, P  = 0.064 and PFS 4.0 versus 5.0 months, HR = 1.47, 95% CI 1.05–2.07, P  = 0.024). In patients with mCRPC receiving second-line therapies, a significant treatment interaction was observed between plasma AR and cabazitaxel versus AR-directed therapies for OS ( P  = 0.041) but not PFS ( P  = 0.244). In an exploratory analysis, AR -gained patients treated with initial reduced dose of cabazitaxel had a significantly shorter median OS (7.3 versus 11.5 months, HR = 1.95, 95% CI 1.13–3.38, P  = 0.016) and PFS (2.7 versus 5.0 months, HR = 2.27, 95% CI 1.39–3.71, P  = 0.001). Conclusion: Plasma AR status has a potential clinical utility in patients being considered for cabazitaxel. Validation of these findings in prospective trials is warranted. Highlights: Plasma AR status has a clinical utility in patients being considered for cabazitaxel. In second-line therapy, plasma AR gain may be useful for treatment selection. Significant interaction of second-line therapy and AR status has been shown for overall survival. The initial cabazitaxel dose has a potential prognostic role, especially in AR-gained patients.